Who will I be when I retire? Introducing a Lacanian typology at the intersection of present identity work and future narratives of the retired self. (February 2019) - Driver, Michaela
The study introduces a framework by which insights from Lacanian psychoanalysis can be employed to offer a more nuanced understanding of how retirement is currently being reinvented. Building on an analysis of 49 stories in which early-career employees describe their retirement aspirations, the study explores the complexities of how individuals draw on retirement discourse to articulate who they are and what they want. The analysis suggests that the narrative construction of retirement is not only a space for becoming further attached to fantasies that align identity with existing power structures but also a space in which to work through such attachments and open up identity in transformative ways. The study contributes novel perspectives on the effects of the contradictions in current retirement discourse at the interstice of identity, discourse and power, offering new avenues for research on retirement and identity.